Sistem Pemerintahan Indonesia: Pendekatan Teori dan Praktik - Ahmad Yani (University of Jember, 2018)
Abstract Indonesia’s presidential system requires the separation of powers (executive, legislative and judiciary) as it is based on checks and balances. It is stated in the Indonesian Constitution, but it still needs further reform, particularly on the limitation of such tripartite powers. This article uses legal research to analyse and discuss theoretical and practical issues on the governmental system of Indonesia. Theoretically, the authority of state institutions in Indonesia encourages an executive-centered government system. In fact, in carrying out functions and authorities, state institutions do not reflect that the Indonesian system of government embraces the separation of powers. In addition, this study recommends the need for refinement and improvement efforts, to enforce ideal concept and practice. Keywords: Theory and Practice, Governmental System, Indonesia